Negotiation - "Taylor, Margot" (New Delhi, 2003)
Negotiating is a complex and challenging skill and a fundamental part of the work of all lawyers. To succeed as a lawyer, you must be able to negotiate effectively. To be effective, you must understand the psychology which underpins the various strategies and tactics used when negotiating.You must also be able to use this understanding effectively.This manual provides a comprehensive guide to negotiating effectively based on an understanding of the factors which influence legal negotiations and research on what is and is not effective. It combines clear explanations of the strategies and tactics used with detailed practical guidance on howto prepare and conduct a negotiation.Detailed and comprehensive guidance is given on how to structure a negotiation and how to use and respond to argument, offers, demands, strategies, and tactics to achieve a successful outcome.
Keywords: Negotiation-Law